2006
DOI: 10.1590/s1413-86702006000500011
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus (RSV) in infants hospitalized for acute lower respiratory tract disease: incidence and associated risks

Abstract: Respiratory syncytial virus (RSV) is one of the main causes of acute lower respiratory tract infections worldwide. We examined the incidence and associated risks for RSV infection in infants hospitalized in two university hospitals in the state of São Paulo. We made a prospective cohort study involving 152 infants hospitalized for acute lower respiratory tract infections (ALRTI) in two university hospitals in Campinas, São Paulo, Brazil, between April and September 2004. Clinical and epidemiological data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 27 publications
7
21
0
4
Order By: Relevance
“…Nos surtos epidêmicos de VRSH foi observado um padrão dependente da temperatura e nenhuma associação com precipitação pluviométrica, com picos nos meses mais frios do ano. Esse padrão dos surtos de VRSH é semelhante àquele observado por outros autores 18,19 …”
Section: Discussionunclassified
“…Nos surtos epidêmicos de VRSH foi observado um padrão dependente da temperatura e nenhuma associação com precipitação pluviométrica, com picos nos meses mais frios do ano. Esse padrão dos surtos de VRSH é semelhante àquele observado por outros autores 18,19 …”
Section: Discussionunclassified
“…Immunofluorescence (IF), on the other hand, is widely used to detect RSV in epithelial nasopharyngeal cells because it is faster and less laborious than isolation. However, the IF technique requires a sample rich in cells, expertise in handling an immunofluorescence microscope 10 and is less sensitive than RT-PCR 18,20,22 . Our in house RT PCR could detect as few as 100 RSV copies, and this analytic sensitivity is similar to RT assays used in other studies 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory syncytial virus (RSV) is considered to be the most common viral agent of lower respiratory tract infections in infants and young children, and can cause serious respiratory illnesses 5,7,12,20 .The highest morbidity rates are observed in infants, in the elderly and in the immunocompromised 4,9,17,18,22 . Viral isolation in cell cultures continues to be considered the most definitive test for diagnosis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This model achieved a low AUC of 66%, a sensitivity of 80%, a low specificity of 68%, a positive predictive value of 82%, and a low negative predictive value of 66%. For infants hospitalized for acute lower respiratory tract disease, Riccetto et al [126] identified several risk factors for RSV infection: gestational age < 35 weeks, birth weight ≤ 2.5 kg, mother has less than five years of school education, and pulse oximetry < 90% upon hospital admission time.…”
Section: Identifying Rsv Infectionmentioning
confidence: 99%